Magnetization reversal in YIG/GGG(111) nanoheterostructures grown by laser molecular beam epitaxy. Issue 1 (1st January 2017) - Krichevtsov, Boris B.; Gastev, Sergei V.; Suturin, Sergey M.; Fedorov, Vladimir V.; Korovin, Alexander M.; Bursian, Viktor E.; Banshchikov, Alexander G.; Volkov, Mikhail P.; Tabuchi, Masao; Sokolov, Nikolai S.
Abstract: Thin (4–20 nm) yttrium iron garnet (Y3 Fe5 O12, YIG) layers have been grown on gadolinium gallium garnet (Gd3 Ga5 O12, GGG) 111-oriented substrates by laser molecular beam epitaxy in 700–1000 °C growth temperature range. The layers were found to have atomically flat step-and-terrace surface morphology with step height of 1.8 Å characteristic for YIG(111) surface. As the growth temperature is increased from 700 to 1000 °C the terraces become wider and the growth gradually changes from layer by layer to step-flow regime. Crystal structure studied by electron and X-ray diffraction showed that YIG lattice is co-oriented and laterally pseudomorphic to GGG with small rhombohedral distortion present perpendicular to the surface. Measurements of magnetic moment, magneto-optical polar and longitudinal Kerr effect (MOKE), and X-ray magnetic circular dichroism (XMCD) were used for study of magnetization reversal for different orientations of magnetic field. These methods and ferromagnetic resonance studies have shown that in zero magnetic field magnetization lies in the film plane due to both shape and induced anisotropies. Vectorial MOKE studies have revealed the presence of an in-plane easy magnetization axis. In-plane magnetization reversal was shown to occur through combination of reversible rotation and abrupt irreversible magnetization jump, the latter caused by domain wall nucleation and propagation. The field at which the flip takes place depends on the angle between the applied magnetic field and the easy magnetization axis and can be described by the modified Stoner–Wohlfarth model taking into account magnetic field dependence of the domain wall energy. Magnetization curves of individual tetrahedral and octahedral magnetic Fe 3+ sublattices were studied by XMCD. Abstract :